Synthesis of TiO₂ different phase by DC magnetron sputtering - Dobrovolskiy, A.; Goncharov, A.; Kostin, E.; Frolova, E. (Вопросы атомной науки и техники, 2014)
The enhanced interest to synthesis of thin and extra-thin films using for surface materials modification continue to be quite actual up to now. A special attention is drawn to coatings having important for practical applications characteristics with costs-effective production. These may be the films of binary compounds of certain metals, particularly, titanium nitride and titanium oxide. The last compound possesses the utmost significance due to wide range of its unique physical, chemical and biological properties. Functional coatings of titanium dioxide synthesis with nanoscale thickness is of considerable interest since it allows essential economy of the material and the increase of manufacturing productivity with the decrease of production cost. To create a scientific basis of nanotechnologies researchers explore different coatings methods, including the ion-plasma methods. Among them, reactive magnetron sputtering seems to be promising: DC magnetron coating allows to deposit titania in amorphous and crystal phase and control results by variation of deposition conditions. The substrate material influences coating phase, as well as discharge characteristics. The thermal linear expansion coefficient does not influence line blue shift in Raman spectra of deposited films in our experiments. The influence of film annealing after deposition up to 800ºC on dioxide crystalline phase of the film is shown. В настоящее время продолжает сохраняться значительный интерес к созданию тонких и сверхтонких пленок, модифицирующих поверхностные свойства материалов. Особое внимание уделяется покрытиям, имеющим важные для практического применения характеристики при невысокой себестоимости процесса их синтеза. К таким можно отнести пленки бинарных соединений некоторых химически активных металлов, например, нитридов и оксидов титана. Последние имеют особое значение в силу широкого спектра уникальных физико-химических и биологических характеристик. Отдельный интерес представляет получение функциональных пленок диоксида титана наноразмерной толщины, что позволяет существенно экономить материал и ускорять осаждение покрытий при снижении их себестоимости. В процессе создания научных основ современных нанотехнологий используются различные методы осаждения покрытий, в том числе и ионно-плазменные. Среди них перспективными являются методы реактивного магнетронного осаждения. Осаждение в DC-магнетроне позволяет синтезировать покрытия из диоксида титана в аморфной и кристаллической фазах в зависимости от условий осаждения. Материал подложки оказывает влияние на возможность получения рутила наряду с условиями осаждения. Изменение в широких пределах линейного коэффициента термического расширения подложки не оказывает существенного влияния на сдвиг линий рамановского спектра пленок анатаза. Показано влияние отжига в воздухе до 800ºС после осаждения на полиморфную модификацию диоксида титана в пленках. Останнім часом зберігається підвищена увага до створення тонких та надтонких плівок, що змінюють по¬верхневі властивості матеріалів. Особлива увага приділяється покриттям, що демонструють характеристики, важливі для практичного застосування. До таких можна віднести плівки бінарних сполук деяких хімічно активних металів, наприклад, нітридів та оксидів титану. Останні мають особливе значення через широкий спектр їх унікальних фізико-хімічних та біологічних характеристик. Окрему зацікавленість викликає одержання функціональних плівок двоокису титану нанорозмірної товщини. Це дозволяє суттєво економити матеріал та пришвидшити осадження покриттів з одночасним зменшенням їх собівартості. У процесі створення наукових основ сучасних нанотехнологій використовуються різні методи осадження покриттів, зокрема й іонно-плазмові. Серед них перспективними є методи реактивного магнетронного осаджен¬ня. Осадження в DC-магнетроні дозволяє синтезувати покриття з двоокису титану в аморфній або кристалічній фазах у залежності від умов осадження. Матеріал підкладки впливає на можливість утворення з рутилу на рівні з умовами осадження. Зміни в широкому діапазоні лінійного коефіцієнта термічного розширення суттєво не впливають на зсув ліній раманівського спектра плівок анатазу. Показано також вплив відпалювання в повітрі до 800ºС після осадження на поліморфну модифікацію двоокису титану в плівках.